The Countess of Saint Geran : Celebrated Crimes - Dumas, Alexandre, 1802-1870 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Countess de Saint-Geran" by Alexandre Dumas is a historical novel written in the early 19th century. This tale revolves around a complex web of intrigue, crime, and familial relations in the context of 17th-century France, specifically focusing on the lives and misfortunes of the noble families involved. At the start of the novel, we are introduced to a captivating incident in the year 1639, where a troop of horsemen arrives in a village with a prisoner, the young and distinguished Marquis de Saint-Maixent, who is charged with grave crimes. The villagers speculate on his situation, while the marquis himself begins to charm the locals despite his predicament. The narrative then unfolds through a series of dramatic events involving secret escape plans and romantic entanglements, ultimately leading to a scandalous set of circumstances that intertwines the lives of the nobility, specifically the Count and Countess de Saint-Geran, as their family$1 (Bs future hangs in the balance amidst threats of exposure and the desperate actions of the marquis. (This is an automatically generated summary.)s
Release date is 2006-02-28
Produced by David Widger
Keywords: Crime